URGENSI PENDIDIKAN ISLAM NON-DIKOTOMI DI ERA SOCIETY 5.0 - Anang Fahrur Rozi; Rosy Alfiana Dewi; Ikhyaul Khoiri Fatah; Mahmud Mahmud; Madekhan Madekhan (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
As a part of the education system in Indonesia, Islamic education faces various problems and challenges in the era of Society 5.0. The era of Society 5.0. This reality demands an open mindset towards the development of science and technology. One of the challenges of Islamic education in Society 5.0 is that there is still a dichotomy in both science and education management. This study of the idea of non-dichotomous Islamic education uses a descriptive qualitative approach that is based on a literature review. This article argues that Islamic education should make a de-dichotomy effort with a disruptive mindset approach, reshape or create, and self-driving. The renewal of Islamic education is carried out with an integrative-interconnective scientific approach through regulatory aspects and curriculum development.